Analysis and reconstruction of student worksheets based on vee diagrams of biotechnology concept - Tamba, Rhodentia Sri Hastuti; Supriatno, Bambang (Assimilation: Indonesian Journal of Biology Education, 2024)
Planning is needed in practicum to connect students' conceptual and procedural knowledge through well-structured of student worksheets (SW). This can be achieved by using the Vee diagram. Vee diagram is a model that describes the relationship between conceptual and procedural understanding in building scientific knowledge. Through Vee diagrams, students can learn that knowledge comes from events/problem objects. This study aims to analyze and reconstruction student worksheets on Biotechnology concepts focused on making yogurt in several High School Biology textbooks. Method of this study is a descriptive-qualitative method through the stages of ANCOR (Analysis, Trial and Reconstruction). Samples were taken using a purposive method. Research shows that based on results of analysis of 6 student worksheets from various publishers referring to aspects of relevance to the curriculum, structural, practical, and knowledge construction aspects of Vee diagrams, respectively, 71%, 68%, 79% (good category) and 50% (fairly good category). Thus, it can be concluded that in general, the student worksheets are not sufficiently capable of meeting the demands of the curriculum and assisting students in constructing knowledge. Therefore, it is necessary to reconstruct and develop student worksheets that have been analyzed and tested to produce better student worksheet that fulfill every aspect specified above.